"The poor were slaves, and the rich masters." The political concept of the people in the Spanish-American press discourse in times of Independence. Issue 2 (4th May 2022) - Morán, Daniel
ABSTRACT: The commemoration of the bicentennial of the independence of Latin America has meant and important renewal in the historiography. Political and cultural history and its links with conceptual history have provided us with novel interpretations. Within these perspectives this research aims to analyze the political uses of the concept of people during the war of independence in the Spanish-American press. The objetive is to understand in a related way the use and complexity of the concept of people in the Buenos Aires, Santiago de Chile and, Lima press from the revolution of May, 1810 in Buenos Aires, the Upper Peru war, the Chilean Independence, and San Martin's Protectorate in Peru (1821-1822). In these varied contexts, the concept of people had different meanings that sought the political legitimacy of the exercise of power among the various political and social actors: for example, a meaning between disqualifying and denigrating as vulgar, populace, lower class, and, on the other hand, a sense alluding to educated or distinguished people of society, different from the mob. In other words, we are witnessing the politicization of the concept according to the contexts, interests, and, the vicissitudes of the war of independence.